Literature Review: Blockchain-Oriented Software Characteristics and New Stream for Software Process Improvement - Al-Ashmori, A. (Institute of Electrical and Electronics Engineers Inc., 2022)
Software process improvement has been through many discussions in the past few decades with relation to the software development alterations. Blockchain-oriented software has been getting more popular, and many recent scholars discussed the suitability of traditional software engineering for the new kind of software. However, the suitability of the current SPI for blockchain-oriented software has not been discussed yet. This paper aims to define the Blockchain-oriented Software characteristics that differentiate it from the traditional software. A literature search was performed considering the studies published up to the date on IEEE Explore, Springer, ACM, ScienceDirect, ProQuest, Web of Science, and emerald insight. A total of 103 studies were found, and only 49 relevant studies met the inclusion criteria. A thematic analysis was performed with an inductive approach to identify 46 distinctive Blockchain-oriented Software characteristics. This result shows the necessity for researchers to devise specific SPI to develop blockchain-oriented software to address its distinctive characteristics, which affect its development and projects. Finally, a new stream for SPI is recommended here to cover Blockchain-oriented Software Process Improvement. Â© 2022 IEEE.